The Influence of Motivation and Learning, Teaching Methods and Means of Education Student Achievement - Sari, Ifit Novita (Economic and Bussiness Faculty, Dr Soetomo University, 2016)
Abstract.setting the whole student STIENU trate Gresik as the study population. Distributing questionnaires planned and carried out in August 2015. As a sample, so much as the entire population sampled, collected as many as 66 questionnaires were then conducted proving the hypothesis through multiple linear regression techniques. The results showed that F count> F table (147.930> 2,753) with the support of significance (p) <0.05; or in other words proved that together independent variables in this study consists of motivation sailed (X1), the learning method (X2) and education (X3) significantly affects the dependent variable is the student achievement (Y). Taken together learning motivation (X1), the learning method (X2) and education (X3) were able to explain the learning achievement (Y) of 87.1% and only 22.9% were able influenced by other variables outside of this research such as parenting parents, living environment, heredity and so forth. Research also get the fact that it is known from the data analysis where the motivation to learn is the independent variable that gives the greatest influence (49%) to the learning achievement compared with the influence of other variables.